Electric transmission lines: Control and numerical discretization. (17th November 2015) - Göttlich, Simone; Herty, Michael; Schillen, Peter
Summary: We are interested in the mathematical modeling and control of electric power lines. The electric transmission lines under consideration are modeled as directed graph where the evolution of voltage, and current is described by a linear 2 × 2 system of hyperbolic balance laws. Open and closed loop control concepts are investigated for control actions at nodal points in the network. Theoretical and numerical results are presented and compared for different scenarios. Copyright © 2015 John Wiley & Sons, Ltd.